New 8-prenylated quercetin glycosides from the flowers of Epimedium acuminatum and their testosterone production-promoting activities - Zhang, Yixin; Zhang, Cheng; Li, Zihan; Zeng, Cheng; Xue, Zhen; Li, Erwei; Li, Gang; Li, Juan; Shen, Guoan; Xu, Chaoqun; Wang, Yuanyue; Ma, Baiping; et al. (Frontiers in Chemistry, 2022)
Phytochemical investigation was carried out for the flowers of Epimedium acuminatum Franchet. by first conducting LC-MS analysis, leading to the identification of 32 compounds. Furthermore, guided by LC-MS profiling, three new 8-prenylated quercetin glycosides (3′-hydroxylikarisoside C, 3′-hydroxylepimedoside E, 3′-hydroxyldiphylloside B), one new anthocyanin (delphinidin-3-O-p-coumaroyl-sophoroside) and six known compounds were isolated from the flowers of E. acuminatum for the first time, and their structures were characterized based on spectroscopic methods including 1D and 2D NMR, and HRESIMS. Combining our discoveries and literature survey, a revised classification of Epimedium flavonols was proposed as Type A (8-prenylated kaempferol based), which was further subdivided into subtype icaritin and subtype demethylicaritin, and Type B (8-prenylated quercetin based), which was further subdivided into subtype 3′-hydroxylicaritin and subtype 3′-hydroxyldemethylicaritin. The structure-activity relationship (SAR) study was carried out by comparing testosterone production-promoting activities of all the new compounds along with nine related Epimedium flavonols, revealing that the new 8-prenylated quercetin glycosides (subtype 3′-hydroxyldemethylicaritin in Type B) exhibited lower testosterone production-promoting activities in rat primary Leydig cells than Epimedium flavonols of subtype demethylicaritin in Type A, but possessed higher activities than the Epimedium flavonols of subtype icaritin in Type A. These results suggested that either methylation at C-4′ position or hydroxylation at C-3′ position of ring B could significantly reduce the testosterone production-promoting activities of Epimedium flavonols.